Defining the Undefinable Treating Atheism, Agnosticism, and Secular Humanism as Religion for Conscientious Objection, Tax Exemption, and Party-List Registration Purposes (Philippine Law Journal, 2018)
Religion is undefined in the Constitution and in the statutes. Definitions of religion that can be found in cases decided by the Philippine Supreme Court, aside from being mere obiter dicta, are highly theistic. In Aglpay v. Ruip the Court defined religion as "a profession of faith to an active power that binds and elevates man to his Creator." In American Bible Society v. City of Manila, religion was defined as "having reference to one's views of his relations to His Creator and to the obligations they impose of reverence to His being and character, and obedience to His Will."